Intrinsic motivation as a mediator between metacognition deficits and impaired functioning in psychosis. (12th January 2016) - Luther, Lauren; Firmin, Ruth L.; Vohs, Jenifer L.; Buck, Kelly D.; Rand, Kevin L.; Lysaker, Paul H.
Abstract : Objective: Poor functioning has long been observed in individuals with psychosis. Recent studies have identified metacognition – one's ability to form complex ideas about oneself and others and to use that information to respond to psychological and social challenges–as being an important determinant of functioning. However, the exact process by which deficits in metacognition lead to impaired functioning remains unclear. This study first examined whether low intrinsic motivation, or the tendency to pursue novel experiences and to engage in self‐improvement, mediates the relationship between deficits in metacognition and impaired functioning. We then examined whether intrinsic motivation significantly mediated the relationship when controlling for age, education, symptoms, executive functioning, and social cognition. Design: Mediation models were examined in a cross‐sectional data set. Methods: One hundred and seventy‐five individuals with a psychotic disorder completed interview‐based measures of metacognition, intrinsic motivation, symptoms, and functioning and performance‐based measures of executive functioning and social cognition. Results: Analyses revealed that intrinsic motivation mediated the relationship between metacognition deficits and impaired functioning (95% CI of indirect effect [0.12–0.43]), even after controlling for the aforesaid variables (95% CI of indirect effect [0.04–0.29]). Conclusions: Results suggest that intrinsic motivation may be a mechanism that underlies the link between deficits in metacognition and impaired functioning and indicate that metacognition and intrinsic motivation may be important treatment targets to improve functioning in individuals with psychosis. Practitioner points: The findings of this study suggest that deficits in metacognition may indirectly lead to impaired functioning through their effect on intrinsic motivation in individuals with psychosis. Psychological treatments that target deficits in both metacognition and intrinsic motivation may help to alleviate impaired functioning in individuals with psychosis. Limitations : The cross‐sectional design of this study is a limitation, and additional longitudinal studies are needed to confirm the direction of the findings and rule out rival hypotheses. Generalization of the findings may be limited by the sample composition. It may be that different relationships exist between metacognition, intrinsic motivation, and functioning in those with early psychosis or among those in an acute phase or who decline treatment.